2007
DOI: 10.1142/s0218271807011656
|View full text |Cite
|
Sign up to set email alerts
|

Long Range Gravity Tests and the Pioneer Anomaly

Abstract: Experimental tests of gravity performed in the solar system show a good agreement with general relativity. The latter is however challenged by the Pioneer anomaly which might be pointing at some modification of gravity law at ranges of the order of the size of the solar system. As this question could be related to the puzzles of "dark matter" or "dark energy", it is important to test it with care. There exist metric extensions of general relativity which preserve the well verified equivalence principle while p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…First of all, the Gaia mission is expected to provide an estimate of the γ PPN parameter at the level of 10 −6 [197] by measuring the deflection of the light on a 5 years timescale. Furthermore, in addition to this global determination of a global PPN parameter from observations of light deflection, it has been proposed to use Gaia observations to map the deflection angle in the sky and to look for a dependence of the γ PPN parameter with respect to the Sun impact parameter [198][199][200][201][202]. Such a dependence of the gravitational deflection with respect to the observation geometry is also a feature predicted by SME as shown in [82].…”
Section: The Gaia Missionmentioning
confidence: 97%
“…First of all, the Gaia mission is expected to provide an estimate of the γ PPN parameter at the level of 10 −6 [197] by measuring the deflection of the light on a 5 years timescale. Furthermore, in addition to this global determination of a global PPN parameter from observations of light deflection, it has been proposed to use Gaia observations to map the deflection angle in the sky and to look for a dependence of the γ PPN parameter with respect to the Sun impact parameter [198][199][200][201][202]. Such a dependence of the gravitational deflection with respect to the observation geometry is also a feature predicted by SME as shown in [82].…”
Section: The Gaia Missionmentioning
confidence: 97%
“…Work on the third phase was also initiated [55, 106, 309, 379, 391]. Mission studies conducted in 2004–2005 [106] have identified two options: i) an experiment on a major mission to deep space capable of reaching acceleration sensitivity similar to that demonstrated by the Pioneers and ii) a dedicated mission to explore the Pioneer anomaly that offers full characterization of the anomaly.…”
Section: Efforts To Explain and Study The Anomalymentioning
confidence: 99%
“…Significant progress was accomplished concerning the first and second phases [252,307,384,396]. Work on the third phase was also initiated [47,94,313,384,393]. Mission studies conducted in 2004 -2005 [94] have identified two options: i) an experiment on a major mission to deep space capable of reaching acceleration sensitivity similar to that demonstrated by the Pioneers and ii) a dedicated mission to explore the Pioneer anomaly that offers full characterization of the anomaly.…”
Section: A Mission To Explore the Pioneer Anomalymentioning
confidence: 99%